Study of Amino Acid Interaction with a Non-Ionic Surfactant at Different Temperatures - Partap, Ram; Swaroop, Neelam (Asian Journal of Chemistry, 2016)
The surface and thermodynamic parameters iso-octyl phenoxy polyethoxy ethanol (TX-100) with/without α-amino acid, viz., glycine, alanine and phenylalanine have been reported at 288.15, 293.15 and 298.15 K. Thermodynamic parameters indicate that the processes are endothermic in nature but negative values of ΔG°mic and positive ΔS°mic favour the process of micellization.